Clinical profile of post flood fever in a tertiary care hospital in Kerala - T., Bhagyanath; Joseph, Anoop; Jacob, Jacob K.; Samuel, Suma; Kurup, Rakhi R.; Ravindran, Reshnu (International Journal of Research in Medical Sciences, 2021)
Background: Floods are an important source of infection epidemic worldwide. Analysis of different infections presenting during floods can lead us to have a unified approach during such periods. Methods: This study describes the clinical features of fever patients presented to a tertiary care hospital in Kerala after the 2018 flood. Clinical findings of the confirmed leptospirosis cases were also compared with non-leptospirosis cases. Results: A total of 48 patients with fever and myalgia were studied and majority of them were males (77%). 40 patients had contact with contaminated water. But only 10 of them had taken prophylactic doxycycline. Complications were seen less among those who took prophylactic doxycycline. The mean time from the first symptom to first medical care was 4.4 days. Leptospirosis was seen among 15 patients and 2 patients had dengue fever. Hepatic involvement and renal involvement were seen significantly higher among leptospirosis patients. Conclusions: This study emphasized the importance of prophylactic doxycycline and early initiation of antibiotics during flood outbreaks. Awareness among treating doctors and patients is required for the control of outbreaks and prevention of mortality during floods.